Increased glymphatic system activity in patients with mild traumatic brain injury - Dai, Zhuozhi; Yang, Zhiqi; Li, Zhaolin; Li, Mu; Sun, Hongfu; Zhuang, Zerui; Yang, Weichao; Hu, Zehuan; Chen, Xiaofeng; Lin, Daiying; Wu, Xianheng (Frontiers in Neurology, 2023)
Purpose: This study aims to investigate the glymphatic system activity changes in patients with mild traumatic brain injury (mTBI), particularly in MRI-negative patients, using analysis along the perivascular space (ALPS) technology. Methods: A total of 161 mTBI patients (age: 15-92 years old) and 28 healthy controls (age: 15-84 years old) were included in this retrospective study. The mTBI patients were divided into MRI-negative and MRI-positive groups. ALPS index was calculated automatically using whole-brain T1-MPRAGE imaging and diffusion tensor imaging. The Student’s t and chi-squared tests were performed to compare the ALPS index, age, gender, course of disease, and Glasgow Coma Scale (GCS) score between groups. Correlations among ALPS index, age, course of disease and GCS score were computed using Spearman’s correlation analysis. Results: Increased activity of the glymphatic system was suggested in mTBI patients based on ALPS index analysis, including the MRI-negative patients. There was a signiﬁcant negative correlation between the ALPS index and age. In addition, a weak positive correlation between the ALPS index and course of disease was also observed. On the contrary, there was no signiﬁcant correlation between the ALPS index and sex nor between the ALPS index and GCS score. Conclusion: Our study demonstrated that the activity level of the glymphatic system was enhanced in mTBI patients, even when their brain MRI scans were negative. These findings may provide novel insights for understanding the pathophysiology of mild TBI.